Finding precursory air traffic management safety metrics using exploration of trajectory radar tracks - Barragán Montes, Rocío Barragán; Gómez Comendador, Victor Fernando; Sáez Nieto, Francisco Javier; Pérez Sanz, Luis (American Society of Civil Engineers (ASCE), 2018)
The definition of a set of precursory safety metrics is critical to detect when an airspace is degrading in terms of safety and thus undesired effects are becoming more likely. Furthermore, safety metrics are paramount in the measurement of the impact of new operational procedures or technical improvements in the air traffic control system. The study presented in this paper introduces three safety metrics (reaction time performance indicator, time to closest point of approach performance indicator, and time to closest point of approach critical limit ratio) derived from a given airspace and a sizable, assorted traffic sample extracted from traffic surveillance track data. The metrics are used to characterize the airspace as a function of the safety outcome, which can be continuously overseen. The final goal of the safety metrics is to be used as an airspace safety warning system, where precursory metrics would signal the need to act to maintain the air traffic control system safety target in the face of operational, organizational, technical, or legal changes.